A comparison of the therapeutic and reactivating efficacy of newly developed bispyridinium compounds (K206, K269) with currently available oximes against tabun in rats and mice - Kassa, Jiri; Karasova, Jana; Bajgar, Jiri; Kuca, Kamil; Musilek, Kamil (Journal of enzyme inhibition and medicinal chemistry, 2008)
The potency of newly developed bispyridinium compounds (K206, K269) in reactivating tabun-inhibited acetylcholinesterase and eliminating tabun-induced lethal toxic effects was compared with commonly used oximes (obidoxime, trimedoxime, the oxime HI-6) using in vivo methods. Studies which determined percentage of reactivation of tabun-inhibited blood and tissue AChE in poisoned rats showed that the reactivating efficacy of both newly developed oximes is comparable with obidoxime and trimedoxime in blood but lower than the reactivating potency of trimedoxime and obidoxime in the diaphragm and brain. Nevertheless, the differences in reactivating efficacy of obidoxime, trimedoxime and K206 was not significant while the potency of K269 to reactivate tabun-inhibited acetylcholinesterase was significantly lower. Both newly developed oximes were also found to be relatively efficacious in elimination of the lethal toxic effects in tabun-poisoned mice. Their therapeutic efficacy corresponds to the therapeutic potency of obidoxime. The oxime HI-6, relatively efficacious against soman, did not seem to be an adequately effective oxime in reactivation of tabun-inhibited AChE and to counteract lethal effects of tabun. Both newly developed oximes (K206, K269) are significantly more efficacious in reactivating tabun-inhibited AChE in rats and to eliminate lethal toxic effects of tabun in mice than the oxime HI-6 but their reactivating and therapeutic potency does not prevail over the effectiveness of currently available obidoxime and trimedoxime and, therefore, they are not suitable for their replacement of commonly used oximes for the treatment of acute tabun poisoning.
Keywords: aktivace enzymů; Animals; pyridiny; Acetylcholinesterase; Lethal Dose 50; Enzyme Activation; oximy; Pyridinium Compounds; Molecular Structure; pyridinové sloučeniny; LD50; Mice; myši; molekulární struktura; Oximes; Male; acetylcholinesterasa; Pyridines; krysa rodu Rattus; zvířata; mužské pohlaví; cholinesterasové inhibitory; Cholinesterase Inhibitors; Rats